La liturgie céleste dans Le Paradis de Dante / The Heavenly Liturgy in Dante’s Paradise - Puiu Ioniță (Anastasis: Research in Medieval Culture and Art)
Dante’s Paradise is the place where the soul arrives after having passed through the long path of sacrifice and difficulties which is meant to bring purification in order to be saved. It is the purged space of perfection and pure happiness, where the believers who have washed their clothes in the blood of the Lamb are in harmony, together with the angels, continuously praising the saving and triumphant Holy Trinity. It is the feast of the bog weeding, of the union between Christ and His Church, it is the divine Liturgy which is the union of the saints’ and the angels’ voices who worship the divine glory.